Davy Crockett : young pioneer - Santrey, Laurence; Livingston, Francis (Mahwah, N.J. : Troll Associates, 1983)
Profiles the childhood of Davy Crockett, pioneer and patriot.
4.0
3-6
Keywords: Crockett, Davy, -- 1786-1836 -- Juvenile literature; Crockett, Davy, -- 1786-1836.; Crockett, Davy, -- 1786-1836.; United States. -- Congress. -- House -- Biography -- Juvenile literature; Pioneers -- Tennessee -- Biography -- Juvenile literature; Legislators -- United States -- Biography -- Juvenile literature; Pioneers; Legislators; Pioneers; Legislators; Tennessee -- Biography -- Juvenile literature